Management of Unplanned Resurgery. (May 2014) - Zhang, Limin; Yang, Jianling; Wang, Haiming; Peng, Xiangdong; Qu, Dapeng; Jiao, Suying; Bai, Ruimin; Xin, Qili
Abstract Objective. To analyze the causes of unplanned resurgery, and provide an objective basis for the quality evaluation and improvement of the hospital's medical treatment services. Method. A retrospective analysis of 40 cases of unplanned resurgery in a hospital in 2012 was carried out. Result. The rate of occurrence of unplanned resurgery was 0.55% in the hospital in 2012; the main causes included postoperative bleeding, inconsistency between the results of the intraoperative frozen section examination and the pathological examination, which needed further consultation, and incision dehiscence. The proportions of these were 55%, 13% and 10%, respectively. Conclusion. Our department should strengthen perioperative management; the hospital should consider unplanned resurgery as the focus of medical quality management and strictly implement operation grading management and reauthorization systems to decrease the incidence of unplanned resurgery.